ANALYSIS OF STRATEGIES IN FACING BUSINESS COMPETITION AND PRICING FOR CUSTOMER SATISFACTION AT BOUTIQUE ROSSY, BERBEK, NGANJUK - Istan Wighara Moelyono (Jurnal Scientia, 2023)
In this era of globalization, business competition is inevitable as a result of which competition arises in offering quality products at prices that are able to compete in the market, and good service. Business is one of the pillars of the economy in this life. The current phenomenon that attracts the rampant development of shops. At "Boutique Rossy" Berbek, Nganjuk is one of the shops that pays attention to the compatibility between sales strategies, business competition, and pricing offered to consumers. The purpose of this study is to find out how big the sales strategy, business competition, pricing on consumer satisfaction in "Boutique Rossy" Berbek, Nganjuk. The population in this study was all consumers in "Boutique Rossy" Berbek, Nganjuk, but the sample used was 80 respondents. While the sampling technique uses accidental sampling. Data collection techniques are questionnaires, interviews and observations. Based on the results of the study showed that all independent variables, namely sales strategy, business competition, pricing had a positive and significant effect on consumer satisfaction for store customers. As for the study of each independent variable, there is also a positive and significant influence on the dependent variable. It can be concluded that the independent variables namely sales strategy, business competition, and pricing have a positive and significant influence on the dependent variable i.e. consumer satisfaction.